The transience of travel and time: an exploration of flâneur in Richard Linklater’s Before trilogy - S,, Abisha Jasmine Suganthy; Karunanithi, V. (Penerbit Universiti Kebangsaan Malaysia, 2025)
The primary objective of this research is to analyze and interpret the interplay between the cinematic portrayal of travel and flâneur dynamics in Richard Linklater’s Before trilogy—Before Sunrise (1995), Before Sunset (2004), and Before Midnight (2013). The study explores how travel serves as a narrative device in shaping the characters’ emotional landscapes as they navigate different cityscapes. The figure of the flâneur serves as a crucial framework for understanding the relationship between the individual and the city. Travel becomes a transformative act as Jesse and Céline's serendipitous encounters unfold against the expressive backdrops of Vienna, Paris, and Greece. Their wandering embodies the essence of dérive and urban exploration, moving beyond conventional tourist experiences. Additionally, this research investigates the trilogy's temporal and experimental realism, illustrating how Linklater's depiction of time and transient travel contributes to a hyper-realistic portrayal of relationships and personal growth. By situating the trilogy within the discourse of travel and psychogeography, this study offers a nuanced interpretation of how movement through cities shapes both the narrative and human emotions.